2020
DOI: 10.3390/antibiotics9090591
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs as a Drug Repurposing Strategy for Biofilm Control

Abstract: Persistent infections, usually associated with biofilm-producing bacteria, are challenging for both medical and scientific communities. The potential interest in drug repurposing for biofilm control is growing due to both disinvestment in antibiotic R&D and reduced efficacy of the available panel of antibiotics. In the present study, the antibacterial and antibiofilm activities of four non-steroidal anti-inflammatory drugs (NSAIDs), piroxicam (PXC), diclofenac sodium (DCF), acetylsalicylic acid (ASA) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 53 publications
5
31
1
2
Order By: Relevance
“…The antimicrobial activity of diclofenac sodium salt was described by many authors [ 74 , 75 ]. In this study, the antimicrobial activity of the electrospun pure PCL and DSS-loaded PCL mats was tested against S. aureus and E. coli by the contact method according to ISO 22196:2011.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of diclofenac sodium salt was described by many authors [ 74 , 75 ]. In this study, the antimicrobial activity of the electrospun pure PCL and DSS-loaded PCL mats was tested against S. aureus and E. coli by the contact method according to ISO 22196:2011.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa Soheili et al, 2015;Belfield et al, 2017;Fourie et al, 2017;Ulusoy et al, 2017;Pereira et al, 2018;She et al, 2018;Abidi et al, 2019;Dai et al, 2019;Gerner et al, 2020 Staphylococcus aureus Belfield et al, 2017;Dotto et al, 2017;Xu et al, 2017;Cai et al, 2018;Oliveira et al, 2019;Abbas et al, 2020;Tzeng et al, 2020 Candida spp. Rosato et al, 2016;Fourie et al, 2017;Brilhante et al, 2020;Lin et al, 2020;Santos et al, 2020 Escherichia coli Cattò et al, 2017;Pereira et al, 2018;Leão et al, 2020…”
Section: Biofilm-forming Pathogen Number Of Experimental Studiesunclassified
“…Acetylsalicylic acid Rosato et al, 2016;Yang et al, 2016;Belfield et al, 2017;Dotto et al, 2017;Fourie et al, 2017;Xu et al, 2017;Cai et al, 2018;Abidi et al, 2019;Leão et al, 2020;Lin et al, 2020;Santos et al, (Gerner et al, 2020). A previous report demonstrated that the growth of P. aeruginosa in the presence of salicylate reduced the production of extracellular polysaccharides required for biofilm formation (Pereira et al, 2018 (200,175, and 150 µg/ml, respectively).…”
Section: Nsaid Number Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the activity of different drugs belonging to other therapeutic classes are being evaluated in the drugs-repositioning strategy as antimicrobials [7]. Drugs such as Promazine (phenothiazine antipsychotic), Promethazine (antihistamine), Methyldopa (centrally acting antidepressant), Dobutamine (sympathomimetic) and Diclofenac (NSAIDs) have shown an interesting antimicrobial activity, and for this reason they have been defined as non-antibiotic drugs [8][9][10][11][12]. According to these results, Diclofenac, also known as (2-[2-(2,6-dichloroanilino)phenyl] acetic acid), one of the more effective cyclooxygenase enzymes (COX) inhibitors, was selected for this research.…”
Section: Introductionmentioning
confidence: 99%